2015
DOI: 10.5194/isprsarchives-xl-1-w5-755-2015
|View full text |Cite
|
Sign up to set email alerts
|

On the Realistic Stochastic Model of GPS Observables: Implementation and Performance

Abstract: ABSTRACT:High-precision GPS positioning requires a realistic stochastic model of observables. A realistic GPS stochastic model of observables should take into account different variances for different observation types, correlations among different observables, the satellite elevation dependence of observables precision, and the temporal correlation of observables. Least-squares variance component estimation (LS-VCE) is applied to GPS observables using the geometry-based observation model (GBOM). To model the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The loss of quality of the measurements distorts them; As a result, the positioning accuracy is reduced. The loss of quality is mainly due to the random noise of observations, physical correlations, and unmodelled systematic effects [23,24]. These effects are measured by variance estimation methods and applied to the calculations by the R matrix in the KF algorithm.…”
Section: Variance Estimation Methodsmentioning
confidence: 99%
“…The loss of quality of the measurements distorts them; As a result, the positioning accuracy is reduced. The loss of quality is mainly due to the random noise of observations, physical correlations, and unmodelled systematic effects [23,24]. These effects are measured by variance estimation methods and applied to the calculations by the R matrix in the KF algorithm.…”
Section: Variance Estimation Methodsmentioning
confidence: 99%
“…For more information, refer to [32,33]. The reliability of the resolved ambiguities on the stochastic model was investigated in [34] by comparing the IAR success rate when a nominal and realistic stochastic model for the GPS observables is considered. It was shown that when a realistic stochastic model was used, the IAR success rate on individual frequencies improved by 20%, whether on L1 or L2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the weight matrix of the observables is taken into account to affect the estimated baseline components and their uncertainties. As a result, the estimated baseline uncertainties were evaluated in [34] using a nominal and realistic stochastic model of the GPS observables. The findings demonstrate that employing realistic stochastic model results in realistic baseline component uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The stochastic model represents the statistical characteristics of GPS observables using a variance-covariance matrix, and its misspecification leads to unreliable and non-optimal estimates. The stochastic models for GPS observations can be divided into three general categories: (1) equal-weight models in which the identical variances are selected, (2) elevation-based models in which the weighting of observations is performed, using exponential or trigonometric functions, and (3) SNR-based models in which the weighting of observations depends on the SNR values [11].…”
Section: Introductionmentioning
confidence: 99%
“…So far, various methods have been proposed to determine the VCM. In these methods, the VCM matrix is either defined as diagonal, which results in less accurate positioning, or is defined as fully populated, which results in an excessive increase in the computational load in each iteration of the positioning algorithm [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%